Histopathologic Pattern of Thyroid Disease in 1351 Thyroidectomy Patients - Hussein A. El Shallaly, Gamal Eldin; A. B. Ibrahim, Babiker; M. E. Salih, Modather; M. I. Elhajahmed, Mohamed; F. E. Mohammed, Mohammed; O. M. Daffalla, Reem; E. H. Yassin, Ruaa; M. M. Ahmed, Rayan (Sudan Journal of Medical Sciences, 2022)
BackgroundThyroid disease poses a major clinical problem. Knowledge of the pattern and distribution of thyroid disease is important to establish prevention and treatment protocols. This is hampered by lack of data. MethodsThis is a retrospective descriptive study of histopathology reports on thyroid tissue surgically excised from patients over a 10-year-period (from 2009-2020) at a major teaching hospital. Demographic data on patients included the age, gender, geographical location and ethnic origin. Results A total of 1351 histopathological reports on thyroid patients were studied. Twenty one patients (1.6%) had thyroglossal cysts and 1330 patients (98.4%) had goiters. The mean age was 40.6 years (SD±13.25), (range 11-85years). The majority (88%) were females Most of our patients come from Khartoum (76.3%), followed by White Nile (6.4%), and El Gazira states (4.5%). The commonest ethnic groups affected were the Nuba (11.6%) and Jaalin (8%). The majority of patients (85%) had benign thyroid diseases, and only (15%) had neoplastic disease. Simple multinodular goiter (SMNG) accounted for (78.6%) of benign thyroid disease. Follicular adenoma was the commonest benign neoplasm (98%), whereas papillary carcinoma was the commonest malignant tumour (44.9%), followed by follicular carcinoma and Hurthle cell tumours (43.9%). Medullary and anaplastic carcinomas each accounted for (4.1%) of patients. Conclusions The study identified the histopathological pattern of thyroid disease. SMNG was the commonest benign disease. Follicular and Hurtle cell carcinoma combined were almost as frequent as papillary carcinoma. Prevention of SMNG by iodinization, early detection of thyroid neoplasms, and studies on goitrogens should be activated.